Platform for change : a farm cultural park : guide - Analogique (Firm) (Siracusa : LetteraVentidue, 2019)
Platform for Change' is an observatory on the world of art, architecture and design through the lenses of one of the most influential independent cultural centres of the contemporary art world and one of the most lively projects of the reassessment and rebirth of a dying city: the Farm Cultural Park in Sicily. A book that is also a map and a compass for orienting oneself in constructing the trajectories necessary for imagining and stimulating visions of all sizes, through the mirrored tale of Farm?s inspiring models of Farm and those of the processes that Farm has set in motion.0'Platform for Change' is the across-the-boards narrative of a journey through the breathtaking landscapes of global and local urban regeneration, intelligent community building strategies, cities where citizens take charge of their public spaces. Cities where public and private investments are concentrated on developing places for culture, museums, galleries, libraries, theatres, cinemas and cultural activities: performance events, exhibits, presentations, talks, festivals. The book is an exploration inside the spaces for educating children and adolescents and also inside those destined for most adults, where new models are being experimented for receptive and recreational activities, where it?s becoming always more important to reconceptualize mediation spaces between different ethnic groups, cultures and traditions.0'Platform for Change' is a book that can be read with different paces, speeds and modalities, where the most scientific essay content is intertwined with elementary diagrams and the most educational texts comment on images full of meaning.
Fakulti Senibina dan Ekistik
Keywords: Farm cultural park (Agrigento, Italy).; Art and cities; Farm cultural park (Agrigento, Italy).; Contemporary Art -- The arts Fine and decorative arts